Ball-milling of titanium dioxide and zinc oxide for enhanced UV protection - Yang, Panpan; Wang, Hongxia; Chen, Yuyan; Li, Yanan; Zhang, Jun; Zhang, Chunxiao; Lin, Bao; Wei, Xiaolan (Frontiers in Materials, 2023)
Among various sunscreen materials, zinc oxide and titanium dioxide are excellent physical sunscreen components; however, these two materials tend to aggregate and form micrometer-sized particles that may impact their performance. This study utilizes fine grinding techniques to break up the aggregated oxide particles into small nanoparticles with a narrow size distribution averaging around 200 nanometers in diameter. The ground zinc oxide and titanium dioxide particles exhibit enhanced ability in absorbing and scattering ultraviolet radiation compared to their original state before grinding. Consequently, this research offers innovative concepts as well as approaches towards developing highly efficient yet lowtoxic physical sunscreen components while significantly contributing to the preparation process optimization for mixed material performance.